Analisis Kesesuaian Pengembangan Agrowisata Durian (Durio Zibethinus Murr) di Desa Sarah Raya Kabupaten Aceh Jaya: Analysis of the Suitability of Durio Zibethinus Murr Agrotourism Development in Sarah Raya Village, Aceh Jaya District - Izwar; Jalil, Muhammad; Irawan, Jekki; Putra, Iwandikasyah; Fajri, Maulidil (Jurusan Budidaya Perkebunan, 2024)
Research on the analysis of the suitability of the durian agrotourism area will have a positive impact on the long-term plans of the local government and the community who are planning the Sarah Raya village area as the durian center of Aceh Jaya. This research was carried out in Sarah Raya Village, Pasie Raya District, Aceh Jaya Regency. The method used in this research is quantitative descriptive, aimed at describing findings and measurement data in the field systematically, factually and comprehensively. This research examines the feasibility and suitability of land in Sarah Raya Village for cultivating durian plants as well as the potential and support for developing durian agrotourism areas in Sarah Raya Village. Indicators and field observation results show an annual average temperature of 26.1 °C in 2021-2022, relative humidity of 80% in 2022, Andosol soil type, altitude of 200-600 m above sea level, and rainfall of 3175.9 mm in 2021-2022, while Ph is in a neutral position of 5-7, the results of these measurements show that Sarah Raya Village is very suitable as a durian agro-tourism area, apart from that the potential and community support for the development of agro-tourism in Sarah Raya Village is very positive. This can be seen from the average response of 71% of respondents who gave a positive response to the development of agro-tourism areas.